PENGARUH LOKASI TERHADAP REVISIT DENGAN MEDIASI KEPUASAN KONSUMEN DAN MEDIATOR CITRA RASA DAN HARGA PADA PRODUK TEH PUCUK HARUM - Rasipan; Indah Ramadhaniah; Syeila Melani; Elisah; Surya Bintarti (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
The rapid development of the times has made people's lifestyles prioritize practicality so they prefer fast food and drinks such as packaged tea. The data shows that within five years (2018-2022) The Pucuk Harum occupies the first position in the top brand award of the tea category in packaging. The purpose of this study was to examine the effect of location on revisit by mediating consumer satisfaction and taste and price image mediators in Teh Pucuk Harum drink. This research was conducted using quantitative methods. The population of this study is the Bekasi District community with a total sample of 55 respondents. Data collection was carried out using a questionnaire and analyzed with the help of the SmartPLS 3.0 program. This study shows that location is moderated by taste image has no effect on consumer satisfaction, location is moderated by price has no effect on customer satisfaction, but the location moderator variable has a direct effect as a latent variable on customer satisfaction and location mediated by customer satisfaction has an effect on revisit